Pengaruh Harga, Brand Image dan Brand Awareness Terhadap Keputusan Penggunaan Layanan Jasa Transportasi Online InDrive di Balikpapan - Fitriana, Fitriana; Maulana, Ade Agus Putra; Septyarini, Dewi Nur (Visioner : Jurnal Manajemen dan Bisnis, 2025)
This study aims to examine the influence of price, brand image and brand awareness on the decision to use InDrive online motorcycle taxi in Balikpapan partially and simultaneously. The study’s sample consisted of 96 individuals who had used Balikpapan’s InDrive online motorbike taxi service. This research utilizes multiple linear regression analysis as the analytical approach. According to the partial test results price had neither a negative or insignificant effect on the use decision obtained tcount value of -1.070 <  ttable 1.661 and a significance value of 0.287 > 0.05. Brand image positively and significantly influences use decisions, obtained tcount  value of 4.490 > from ttable 1.661 and a significance value of 0.000 < 0.05. Brand awareness contributes positively and significantly on use decisions, obtained tcount  is 6,734 > from ttable 1.661 and the significance value is 0.000 < 0.05. Simultaneously, the price, brand image,  brand awareness significantly influence the decision to use, obtained  Fcount is 84.271 > Ftable 2.70 and the significance value is 0.000 < 0.05.